Can antibiotic De-escalation Be Measured Without Chart Review? A Proposed Electronic Definition. (4th October 2017) - Moehring, Rebekah W; Ren, Xinru; Anderson, Deverick J; Davis, Angelina; Dyer, April; Lokhnygina, Yuliya; Hicks, Lauri; Srinivasan, Arjun; Ashley, Elizabeth Dodds
Abstract: Background: Antimicrobial stewardship programs promote de-escalation: moving from broad to narrow spectrum agents and/or stopping antibiotics as more clinical data return. A standard definition of de-escalation objectively applied to electronic data could provide a means to assess stewardship improvement opportunities. Methods: We performed a retrospective cohort study of de-escalation events among five hospitals from the Duke Health System and the Duke Antimicrobial Stewardship Outreach Network using 2016 electronic medication administration record data. Antibiotics were ranked into four categories: narrow spectrum (e.g., cefazolin), broad spectrum, extended spectrum, and agents typically targeted for protection (e.g., meropenem). Included patients were cared for on inpatient units, had antibiotic therapy for at least 2 days, and had at least 3 days of hospitalization after starting antibiotics. De-escalation was defined as reduction in either the number of antibiotics or rank measured at two time points: day 1 of initiation of antibiotic therapy and day 5 (or day of discharge if occurring on day 3 or 4). Escalation was an increase in either number or rank of agents. Unchanged was either no change or discordant directions of change in number and rank. For all categories, the outcome was percent among qualifying admissions. Descriptive statistics were used to describe de-escalation among hospitals, unit type, and ICD-10 diagnoses. Results: Among 39, 226 included admissions, de-escalation occurred in 14, 138 (36%), escalation in 5, 129 (13%), and antibiotics were unchanged in 19, 959 (51%) (Figure). Percent de-escalation was significantly different among hospitals (median 37%, range 31–39%, P < .001). Infectious diagnoses with lower rates of de-escalation included intra-abdominal infection (23%), skin and soft-tissue infection (28%), and ENT/upper respiratory tract infection (19%). Intensive care units had higher rates of both de-escalation and escalation (43% and 16%) when compared with non-ICU wards (35% and 13%, P < .001). Conclusion: We provided an objective, electronic definition of de-escalation and demonstrated variation among hospitals, units, and diagnoses. This metric may be useful for assessing stewardship opportunities. Disclosures: All authors: No reported disclosures.